HUBUNGAN PERSONAL HYGIENE DAN KONDISI LINGKUNGAN DENGAN KEJADIAN DERMATITIS PADA SANTRI - Marlina Marlina (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Skin disease is a disease that attacks the surface of the body, and is caused by various causes. The number of cases of skin disease in Indonesia was 501,280 cases or 3.16%, of which dermatitis reached 67.3%. Based on reports from the work area of the Aek Songsongan Health Center, there were 234 cases of skin diseases. The purpose of this study was to determine the relationship between personal hygiene and environmental conditions with the incidence of dermatitis. The study used an analytic survey method with a cross sectional approach. The research population was all students as many as 523 people with a sample using accidental sampling technique as many as 83 people. Data analysis used univariate and bivariate analysis with chi-square test statistics. The results of the analysis showed that personal hygiene p-value = 0.003 <0.05 and environmental conditions obtained p-value = 0.006 <0.05. The conclusion of this study is that there is a relationship between personal hygiene and environmental conditions with the incidence of dermatitis in students at the Darul Al-Falah Islamic Boarding School, Aek Sosongan District, Asahan Regency in 2020. It is hoped that pesantren managers should renovate the room to meet health requirements, and make policies that regulate environmental health management. and behavior of students to always perform personal hygiene.Keywords: Personal Hygiene